2008
DOI: 10.1136/pgmj.2008.069740
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone resistance

Abstract: Thyroid hormone resistance (THR) is a rare syndrome of reduced end organ sensitivity. Patients with THR have elevated serum free thyroxine (FT4), free triiodothyronine (FT3), but normal or slightly elevated serum thyrotropin values. The characteristic clinical feature is goitre without symptoms and metabolic consequences of thyroid hormone excess. THR can be classified on the basis of tissue resistance into pituitary, peripheral or generalised (both pituitary and peripheral) types. Mutations in the TRbeta gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 33 publications
0
32
0
6
Order By: Relevance
“…However, ␤-blockers do not prevent accelerated osteoporosis, and therefore follow-up with bone mineral density studies and treatment with calcium and vitamin D should be added to this recommendation. There are also data about the usage of thyroid hormone analogs, such as 3,3,5 triiodothyroacetic acid and dextrothyroxine to suppress TSH in RTH (37,39). It was demonstrated that 3,3,5 triiodothyroacetic acid exerts thyromimetic effects predominantly on pituitary and on hepatic tissue (39 -41).…”
Section: Discussionmentioning
confidence: 99%
“…However, ␤-blockers do not prevent accelerated osteoporosis, and therefore follow-up with bone mineral density studies and treatment with calcium and vitamin D should be added to this recommendation. There are also data about the usage of thyroid hormone analogs, such as 3,3,5 triiodothyroacetic acid and dextrothyroxine to suppress TSH in RTH (37,39). It was demonstrated that 3,3,5 triiodothyroacetic acid exerts thyromimetic effects predominantly on pituitary and on hepatic tissue (39 -41).…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis of neonatal thyrotoxicosis includes the McCune-Albright syndrome, activating mutations of the TSH receptor and thyroid hormone resistance syndrome [109, 110]. These non-autoimmune etiologies are rare but should be considered if thyrotoxicosis persists beyond 3 months of age.…”
Section: Graves' Disease (Gd)mentioning
confidence: 99%
“…As ‘thyroid hormone resistance syndrome’ (Agrawal and others 2008) and inappropriate TSH secretion from a pituitary adenoma (TSH-oma) have not been described in dogs, spurious hyperiodothyroninaemia caused by T3-AA and T4-AA was considered the most likely differential diagnosis. In accordance, FT4 measured by equilibrium dialysis (FT4-ED) to exclude methodological artefacts, was below the detection limit of the assay (ruling out ‘thyroid hormone resistance syndrome’ and TSH-oma) and titres for TG-AA, T4-AA and T3-AA (estimated by ELISA, Patzl and Möstl, 2003; see Table 1) were markedly elevated.…”
Section: Investigationsmentioning
confidence: 99%